Negotiating Taboos and Tradition: Multicultural Wisdom in the Coastal Muslim Communities of Pangkalan Buton Village - Hidayat, Samsul; Kurniawan, Syamsul; Nurhaliza, Feni; Maimunah (IBDA` : Jurnal Kajian Islam dan Budaya, 2025)
This article examines the reflection of the multicultural wisdom of coastal Muslim communities in Pangkalan Buton, West Kalimantan. This study adopts a phenomenological approach, utilizing data gathered through direct observation and in-depth interviews. The data analysis process encompasses collection, condensation, and presentation. The findings reveal that the taboos in Pangkalan Buton represent a fusion of Islamic teachings and local values. These taboos operate not exclusively as social norms but as a mechanism for preserving cultural identity in social changes. The community interprets Islam flexibly, adapting its principles to align with local culture and shaping behavioral patterns that foster social harmony. Consequently, taboos have become vital to daily life, striking a balance between religious beliefs and local traditions. The results indicate that many of these taboos correspond with Islamic teachings, illustrating a moderate approach to Islam that accommodates local wisdom. In Pangkalan Buton Village, Islam is accepted flexibly, integrating religious teachings with local customs to promote social harmony.